Association between detection of HIV-1 DNA resistance mutations by a sensitive assay at initiation of antiretroviral therapy and virologic failure - Gonzague Jourdain (2018)
Background. Antiretroviral therapy (ART) has become more available throughout the developing world during the past 5 years. The World Health Organization recommends nonnucleoside reverse-transcriptase inhibitor-based regimens as initial ART. However, their efficacy may be compromised by resistance mutations selected by singledose nevirapine (sdNVP) used to prevent mother-to-child transmission of human immunodeficiency virus (HIV)1. There is no simple and efficient method to detect such mutations at the initiation of ART. Methods. One hundred eighty-one women who were participating in a clinical trial to prevent mother-tochild transmission and who started NVP-ART after they had received sdNVP or a placebo were included in the study. One hundred copies of each patient's HIV-1 DNA were tested for NVP-resistance point-mutations (K103N, Y181C, and G 190A) with a sensitive oligonucleotide ligation assay that was able to detect mutants even at low concentrations (≥5% of the viral population). Virologic failure was defined as confirmed plasma HIV-1 RNA >50 copies/mL after 6 to 18 months of NVP-ART. Results. At initiation of NVP-ART, resistance mutations were identified in 38 (26%) of 148 participants given sdNVP (K103N in 19 [13%], Y181C in 8 [5%], G190A in 28 [19%], and ≥2 mutations in 15 [10%]), at a median 9.3 months after receipt of sdNVP. The risk of virologic failure was 0.62 (95% confidence interval [CI], 0.460.77) in women with ≥1 resistance mutation, compared with a risk of 0.25 (95% CI, 0.17-0.35) in those without detectable resistance mutations (P < .001). Failure was independently associated with resistance, an interval of <6 months between sdNVP and NVP-ART initiation, and a viral load higher than the median at NVP-ART initiation. Conclusions. Access to simple and inexpensive assays to detect low concentrations of NVP-resistant HIV-1 DNA before the initiation of ART could help improve the outcome of first-line ART. © 2010 by the Infectious Diseases Society of America. All rights reserved.